Relationship between disability category, time spent in general education and academic achievement. Issue 4 (3rd July 2020) - Barrett, Courtenay A.; Stevenson, Nathan A.; Burns, Matthew K.
ABSTRACT: Federal law under the Individuals with Disabilities in Education Improvement Act stipulates that services provided to students with diagnosed disabilities must be (a) individualised based on the assessed needs of each student and (b) include the fewest restrictions necessary to achieve students' personalised goals. However, determining the level of service and educational placement best suited to each student can be challenging. Recent legal rulings are also placing increased pressure on schools to provide services that yield substantive achievement. The following study examines the relation between time spent in general education settings and outcomes on state assessments. Results indicate a significant positive association between time spent in general education and scaled scores on state assessments for reading and math; no association was found for alternative state assessments. Ethical and practical implications as well as recommendations for future research are discussed.